PHARMACOLOGICAL PROPERTIES AND THERAPEUTIC POTENTIAL OF ZINGIBER OFFICINALE ROSCOE - Bilovol, O.M.; Kniazkova, I.I.; Chubuchna, I.I.; Kryvoshapka, O.V.; Molodan, D.V.; Kuzminova, N.V.; Abramova, L.P. (World of Medicine and Biology, 2025)
Ginger rhizome is included in the British Herbal Pharmacopoeia, the Pharmacopoeias of China, Japan, Egypt, Austria and Switzerland. The aim of the review is to summarize the literature on the phytochemistry of the main action molecular mechanisms and pharmacological properties of Zingiber officinale Roscoe, as well as the results of studies of its use in the last five years. Numerous studies have shown that ginger contains nutritional components essential for health. Zingiber officinale Roscoe contains a variety of nutrients, such as carbohydrates, amino acids, proteins, vitamins, minerals, fatty acids, lipids, a large number of phytochemicals, especially essential oils and phenolic compounds and other biologically active compounds. The biological activity of ginger and its chemical compounds is promising for the treatment and prevention of diabetes, obesity, nausea, vomiting, and inflammation. Research results have demonstrated potent antioxidant, as well as anti–inflammatory and antiemetic properties, The biological activity of ginger and its chemical compounds is promising for the treatment and prevention of diabetes, obesity, nausea, vomiting, and inflammation. Research results have demonstrated potent antioxidant, as well as anti–inflammatory and antiemetic properties, pregnancy–associated nausea and vomiting of ginger compounds. Findings from studies suggest that Zingiber officinale Roscoe supplements are beneficial for obesity and lipid metabolism disorders, but additional clinical studies are needed to support their efficacy and safety. It has been established that in patients with diabetes mellitus, the supplementation of Zingiber officinale had a positive effect on glycometabolic parameters, some markers of inflammation, oxidative stress, and the progression of kidney damage in diabetic kidney disease.
Keywords: phytotherapy; Zingiber officinale Roscoe; biological activity; pharmacological effects; antiemetic properties; antioxidant activity; аntimicrobial activity